Pengaruh Harga, Kualitas Produk Dan Region Of Origin terhadap Keputusan Pembelian Kaos Cak Cuk di Surabaya - Jailani, Ahmad Syihabuddin (BISMA (Bisnis dan Manajemen), 2018)
T-shirt, will never far from human life due to the need ofwearing it everyday. One of local famous T-shirt demanding by the customers is Cak-Cuk shirt. Cak Cuk is an iconic shirt that represents Surabaya. This research was conducted with a quantitative approach, which aimed to test the influence of price, product quality and region of origin to the purchasing decision. The population in this study were adolescents aged 16-30 years at Jalan Dharmawangsa number 35 Surabaya. Samples taken as much as 83 respondents with judgmental sampling techniques. The analysis tools are Multiple linear regression. The results showed that the influence of price, quality product, and region of origin of the purchasing decisions. The result of hypothesis testing showed that price, product quality, region of origin have partial influence to the purchasing decision